KAJIAN TENTANG KARAKTER KEWARGANEGARAAN (STUDI KASUS PELANGGARAN PENGGUNAAN ENERGI LISTRIK PADA MASYARAKAT KABUPATEN SUKOHARJO) - Dharmawan, Andriyani (PKn Progresif, 2015)
Based on these results, it can be concluded that: (1) The background of the offsen was due Sukoharjo Regency community to the use of electrical energy knowledge factors, economic factors, persuasive factors, and factors of service quality. (2) The connection between violations and civic character are very closely, namely the behavioral deviations by a foul electrical energy without being based on the character of citizenship includes the law abiding character (public character), responsibility (private character), and honest (privat character) as guidance to become good citizens. (3) Solutions to anticipate offense is preventive, repressive, and curative is to educate, nurture, and provide effective learning to society Sukoharjo and streamline the entire system is in PLN. But this can not be realized properly.